COVID 19: Variants, Diagnosis and Vaccines- An Update - Chauhan, Parul; Tiwari, Ankita; Emmanuel, Okoro; Babu, M. Arockia (Coronaviruses, 2024)
In 2019, a life-threatening virus, SARS-Cov 2 emerged in China and caused destruction all around the world, affecting many lives; the origin of this virus is still debatable and unclear. The coronavirus is a contagious disease with high rates of transmission; it mutates rapidly and now has variants, some of which have caused a lot of damage to lives and the economy. These variants are mainly classified into three main groups: a) variants of concern; b) variants of interest; and c) variants under monitoring. Vaccines are the safest and most effective option for preventing covid and saving lives, as building immunity and breaking the chain of transmission is essential even though vaccines that have been developed till now have different effects against different variants of coronavirus. As it is known that vaccines are the main shield to protect from coronavirus, due to rapid mutation and slow developments of vaccines several people are still getting infected with covid-19. Many treatment options are available, such as antiviral drugs, nanotechnology, plasma therapy, and monoclonal antibodies. Besides prevention and treatment, correct diagnosis of the disease is essential, and for this purpose, different diagnostic techniques are discussed in this article alongside the possible future of COVID-19.
Keywords: COVID-19